Treatment outcomes of pulpotomy versus pulpectomy in vital primary molars diagnosed with symptomatic irreversible pulpitis: protocol for a non-inferiority randomised controlled trial - Nebu Philip (14779318) (2024)
Background Pulpectomy continues to be the standard treatment recommendation for management of vital primary molars diagnosed with symptomatic irreversible pulpitis. The recent decade has seen a paradigm shift in the treatment concepts of how vital mature permanent molars diagnosed with irreversible pulpitis can be more conservatively managed using vital pulp therapy techniques like pulpotomy. However, despite emerging evidence indicating similarities between primary and permanent tooth pulp response to dental caries, there is limited research on whether pulpotomy can be similarly used as a definitive treatment modality for vital primary teeth with irreversible pulpitis. This randomised controlled trial (RCT) aims to compare the treatment effectiveness of pulpotomy versus pulpectomy in management of vital primary molars diagnosed with symptomatic irreversible pulpitis over a two-year period. Methods/design This clinical study is a parallel, two-armed, open label, non-inferiority RCT with a 1:1 allocation ratio between the experimental intervention arm (pulpotomy) and the active comparator arm (pulpectomy). Healthy cooperative children, between 4–9 years of age, who have painful primary molars with clinical symptoms typical of irreversible pulpitis will be recruited after obtaining informed consent from their parents/legal guardians. 50 vital primary molars clinically diagnosed with symptomatic irreversible pulpitis will be randomly distributed between the two treatment arms. The primary outcomes that will be assessed are clinical and radiographic success after six-months, one-year and two-years of the trial interventions. The influence of baseline pre-operative variables (age; gender; tooth type; site of caries; pre-operative furcal radiolucency; pre-operative pain intensity) and intra-operative factors (time taken to achieve haemostasis) on treatment outcomes will also be assessed. The secondary outcome evaluated will be the immediate (24 h and 7 d) post-operative pain relief afforded by the two treatment interventions. Discussion This trial seeks to provide evidence on whether pulpotomy treatment can be no worse than the standard pulpectomy treatment for the management of symptomatic irreversible pulpitis in vital primary molars. Trial registration ClinicalTrials.gov (NCT06183203). Registered on 30 January 2024. Other Information Published in: BMC Oral Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s12903-024-04411-6